Land rights and expropriation in ethiopia - Ambaye, Daniel W. (Springer Theses, Recognizing Outstanding Ph.D. Research,, 2015)
This thesis provides a new approach to the Ethiopian Land Law debate. The basic argument made in this thesis is that even if the Ethiopian Constitution provides and guarantees common ownership of land (together with the state) to the people, this right has not been fully realized whether in terms of land accessibility, enjoyability, and payment of fair compensation in the event of expropriation. Expropriation is an inherent power of the state to acquire land for public purpose activities. It is an important development tool in a country such as Ethiopia where expropriation remains the only method to acquire land. Furthermore, the two preconditions of payment of fair compensation and existence of public purpose justifications are not strictly followed in Ethiopia. The state remains the sole beneficiary of the process by capturing the full profit of land value, while paying inadequate compensation to those who cede their land by expropriation. Secondly, the broader public purpose power of the state in expropriating the land for unlimited activities puts the property owners under imminent risk of expropriation.